2010
DOI: 10.2460/javma.237.5.561
|View full text |Cite
|
Sign up to set email alerts
|

Reference intervals and relationships between health status, carapace length, body mass, and water temperature and concentrations of plasma total protein and protein electrophoretogram fractions in Atlantic loggerhead sea turtles and green turtles

Abstract: Reference intervals for concentrations of TP and ELFs for healthy, free-ranging loggerhead sea turtles and green turtles can be used in combination with other diagnostic tools to assess health status of sea turtles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
39
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 11 publications
6
39
2
Order By: Relevance
“…2). In the body, γ-globulins (i.e., antibodies) will increase in response to certain pathogens (Zaias and Cray, 2002); however, the highest γ-globulin concentration from our study (2.26 g/dL) fell within the "normal" reference range for loggerhead turtles (0.48-2.38 g/dL; N = 437 turtles; Osborne et al, 2010). Other studies have reported γ-globulin concentrations outside of this reference range for loggerhead turtles (Gicking et al, 2004: max of 2.98 g/dL for adult females; Deem et al, 2009: 2.88 g/dL for foraging turtles).…”
Section: Brevetoxins and Maternal Healthcontrasting
confidence: 66%
“…2). In the body, γ-globulins (i.e., antibodies) will increase in response to certain pathogens (Zaias and Cray, 2002); however, the highest γ-globulin concentration from our study (2.26 g/dL) fell within the "normal" reference range for loggerhead turtles (0.48-2.38 g/dL; N = 437 turtles; Osborne et al, 2010). Other studies have reported γ-globulin concentrations outside of this reference range for loggerhead turtles (Gicking et al, 2004: max of 2.98 g/dL for adult females; Deem et al, 2009: 2.88 g/dL for foraging turtles).…”
Section: Brevetoxins and Maternal Healthcontrasting
confidence: 66%
“…Abbreviations: AF, adult female; AM, adult male; FF, foraging female; FM, foraging male; JF, juvenile female; JM, juvenile male; NA, not available; NF, nesting female; SF, stranded female; SM, stranded male; and TP, total protein. The studies are numbered as follows: 1, Deem et al (2006) ; 2, Harms et al , 2007 ; 3, Innis et al (2010) ; 4, Harris et al (2011) ; 5, Honarvar et al (2011) ; 6, Perrault et al (2012) ; 7, Gicking et al (2004) ; 8, Deem et al (2009) ; and 9, Osborne et al (2010) . a 1 = TP by clinical chemistry analyser, fractions by electrophoresis; 2 = clinical chemistry analyser; 3 = TP by clinical chemistry analyser, fractions by electrophoresis; 4 = clinical chemistry analyser; 5 = TP by handheld refractometer, fractions by clinical chemistry analyser; 6 = TP by biuret method, fractions by electrophoresis; present study = TP by biuret method, fractions by electrophoresis; 7 = TP by biuret method, fractions by electrophoresis; 8 = TP and globulin by clinical chemistry analyser, fractions by electrophoresis; and 9 = TP by biuret method, fractions by electrophoresis.…”
Section: Resultsmentioning
confidence: 99%
“…This finding may be consistent with the initial debilitation and anaemia often seen in sick and debilitated sea turtles ( Aguirre et al ., 1995 ). Previous studies in rehabilitating loggerheads have shown low PCV and total solids in animals with a variety of illnesses (malnutrition, trauma and toxin exposure), with improvement in values over time with appropriate medical therapy ( Casal and Orós, 2009 ; Deem et al ., 2009 ; Osborne et al ., 2010 ).…”
Section: Discussionmentioning
confidence: 99%